Trial strategy and techniques in highway contract litigation. (Research results digest (National Cooperative Highway Research Program), 1979)
"A report submitted under ongoing NCHRP Project 20-6, "Right-of-Way and Legal Problems Arising Out of Highway Programs," for which the Transportation Research Board is the agency conducting the research."